THE EFFECT OF EFICIENCY RATIO, EFFECTIVENESS RATIO, CONTRIBUTION RATIO OF LAND AND BUILDING TAX ON LOCAL OWN SOURCE REVENUE IN THE SUKOHARJO REGENCY 2016-2018 (EMPIRICAL STUDY IN THE REGIONAL AGENCY OF THE SUKOHARJO REGENCY) - Haryanti, Setyani Sri; Tatok, Febrian Fernanda Siwi; Edy, Irwan Christanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to determine the effect of the efficiency ratio of Land and Building Tax revenue, determine the effect of the effectiveness ratio of Land and Building Tax revenue and determine the effect of the ratio of contribution of Land and Building Tax revenue to Local Government Revenue Original Revenue in Sukoharjo Regency in 2016-2018.The data analysis technique in this study is a descriptive analysis using indicators of the criteria of efficiency, effectiveness and contribution. The type of data used is quantitative data, data sources used secondary data and use the documentation method.The results of the study know that the efficiency ratio of land and building tax revenue in Sukoharjo regency in 2016-2018 is included in the very efficient criteria because in those 3 years the realization of land and building tax revenues is greater than the cost of collection. The effectiveness ratio of revenue from land and building tax in Sukoharjo Regency in 2016-2018 is included in the very effective criteria because the average for 2016-2018 is more than 100%, namely 123.93% with details in 2016 of 131.41% , in 2017 it was 120.35% while in 2018 it was 120.02%. The contribution ratio of the Land and Building Tax to Local Government Revenue in Sukoharjo Regency in 2016-2018 is included in the criteria of lacking because the ratio of contributions on average is only 10.71%.